Exploring principles of unity in cultural diversity: An analytical review on prophet’s Final Sermon and Washington’s Farewell address - Shogar, Ibrahim (Pusat Pengajian Teras, Univeristi Sains Islam Malaysia, 2019)
Background: As the phenomenon of ‘Globalization’ is increasingly becoming dominant, we need to learn how to live with others. In this context, the holy Qur`an reminds the entire mankind about the unity of their origin, either as originated from clay (Qur`an, 23:12, 32:7, 37:11) or from a single person (Adam) (Qur`an, 4:1) or from a single pare of male and female, before being separated into various nations and tribes that they may know each other (Qur`an, 49:13). Using terminologies of social science, we can say: the holy Qur`an is inviting mankind to investigate upon the social and epistemological aspects of the cultural diversity. To achieve this noble goal we need to learn from our heritage, the glorious history of Islamic civilization, challenges facing the contemporary Muslim communities, as well as form the entire human history and the useful experiences of other nations that are consistent with principle objectives of the Islamic worldview. Objectives: this paper aims to investigate principles of unity and cooperation that lead to peace and sustainable development in multicultural societies. Such principles can be formulated based on both: the al-Naqil knowledge (revelation) or the `Aqil knowledge (reason). The first is represented by basic principles of human rights as embodied in the Final Sermon of the Prophet Muhammad (s.as.) (Khubatul Wida`), the second is represented by basic principles of the Farewell Speech of Gorge Washington. Methodology: Although investigation of principles of unity in multi-cultural society can be empirical or theoretical, the method adopted in this paper is theoretical in nature. It analyzes the basic ideas of the above two historic documents to formulate the principles. Religious texts (Qur`an and Sunnah) which related to unity of mankind, peace, and cooperation will be collected and analyzed. The various perspectives of the early Muslim scholars, on such texts will be consulted. Conclusions: the final findings of the paper should emphasize the integrated method of Naqli and `Aqli, instead of pure secular approach, towards formation of principles for unity, cooperation, and sustainable development in multicultural communities, such as in Malaysia.